Problem Based Learning With Multimodal on Students’ Critical Thinking Skills in Work and Energy: A Systematic Literature Review - Tiara Dwi Saiva; Yasfi Ismayani; Gunawan Gunawan (Indonesian Journal of Applied Science and Technology, 2023)
Critical thinking is an essential 21st-century skill in physics learning, particularly for the abstract topic of work and energy. This study systematically reviews the effectiveness of multimodal-based Problem-Based Learning (PBL) in enhancing students' critical thinking skills. A qualitative Systematic Literature Review (SLR) following the PRISMA 2020 guidelines was conducted using studies from Google Scholar, Garuda, SINTA, and Scopus. After applying the inclusion and exclusion criteria, seven studies published between 2014 and 2023 were analyzed. The findings indicate that multimodal-based PBL improves critical thinking by supporting conceptual understanding through multiple representations, such as interactive multimedia, PhET simulations, videos, digital worksheets, and e-modules. Integrating multimodal resources with authentic problem-solving activities enhances students' analytical reasoning, evaluation, scientific argumentation, and problem-solving skills. Overall, multimodal-based PBL is an effective instructional approach for developing critical thinking skills in physics learning.